Attitudes Regarding Participation in a Diabetes Screening Test among an Assyrian Immigrant Population in Sweden. (19th December 2016) - Andersson, Susanne; Karlsson, Veronika; Bennet, Louise; Fellbrant, Klas; Hellgren, Margareta
Abstract : Immigrants from the Middle East have higher prevalence and incidence of type 2 diabetes (T2D) compared with native Swedes. The aim of the study was to describe and understand health beliefs in relation to T2D as well as attitudes regarding participation in a screening process in a local group of Assyrian immigrants living in Sweden. A qualitative and quantitative method was chosen in which 43 individuals participated in a health check-up and 13 agreed to be interviewed. Interviews were conducted, anthropometric measurements and blood tests were collected, and an oral glucose tolerance test was performed. In total, 13 of the 43 participants were diagnosed with impaired glucose metabolism, 4 of these 13 had TD2. The interviewed participants perceived that screening was an opportunity to discover more about their health and to care for themselves and their families. Nevertheless, they were not necessarily committed to taking action as a consequence of the screening. Instead, they professed that their health was not solely in their own hands and that they felt safe that God would provide for them. Assyrians' background and religion affect their health beliefs and willingness to participate in screening for TD2.